Biochemical, serological, and genetic aspects related to gene HLA‐DQB1 and its association with type 1 diabetes mellitus (T1DM). Issue 5 (6th March 2020) - Singh, Gur Charn; Ahmed, Mehboob; Zaid, Muhammad; Hasnain, Shahida
Abstract: Background: Type 1 Diabetes Mellitus (T1DM) is the autoimmune disorder of destruction of β cells of pancreas, creating insulin deficiency condition, which leads to hyperglycemia, polyuria, polydipsia, ketoacidosis, and other metabolic disorder especially in children. Different genetic aspects and environmental factors are involved in pathophysiology of the disease. About 20 genes are associated with this disease in which the most common is the different combination of haplotype DRB1‐DQA1‐DQB1 present at HLA gene. At HLA‐DQB1, there are some SNPs which are associated with T1DM. In T1DM, there are number of biochemical, serological parameters which show some abnormalities leading to some complications. Methods: Samples were subjected to all biochemical and serological techniques to get the measurement of concentration of glucose, lipid profile (cholesterol, triglycerides, and HDL and LDL cholesterol), urea, creatinine, albumin, insulin, anti‐insulin antibodies, C‐peptides, and leptin. All these values were compared with controls values and statistical analysis was also done on these values. At molecular level, two primers set which were allele specific at HLA‐DQB1, were used to amplify the SNPs, homozygous and heterozygous conditions were stated. Results: PCR results for the studied population showed that most of samples have heterozygous condition for these SNPs of this allele specific region on HLA‐DQB1. Very few of them have homozygous state for it. Even in the control sample have the same conditions. Conclusion: In Pakistan, there is dire need of studies about SNPs and haplotypes related to HLA‐DQB1 which show association with T1DM. Abstract : Different genetic aspects and environmental factors are involved in the pathophysiology of Type1 diabetes mellitus. About 20 genes are associated with this disease in which the most common is the different combination of haplotype DRB1‐DQA1‐DQB1 present at HLA gene. At HLA‐DQB1, there are some SNPs which are associated with T1DM